Varability in the Content of Internet Forums - Węckowski, Dawid Grzegorz; Kaczmarek, Tomasz (Studia Oeconomica Posnaniensia, 2013)
In this article we present the results of a study conducted on a sample of Polish Web forums in order to investigate how these sites evolve over time. We analysed more than 27 900 Web pages from 16 sources at two hour intervals (4 256 data points) over 22 days of the experiment. Th e results can be the basis for improving Web crawler design, providing valuable insights into the nature of Web forums. It appears that the variability of Web forums content is signifi cantly diff erent from general-purpose Web sites, thus Web crawlers need to adjust their document extraction policies to deal with this kind of Web source.